ACTUATING DALAM ALQURAN - Hadijaya, Yusuf; Harahap, Vena Annisa; Suciyandhani, Adinda (Hijri, 2022)
Actuating is a function as well as a process in the administration of Islamic education. For educational institutions, actuating means mobilizing or directing existing resources for the institution, including human resources and other resources. Integrated efforts to maximize the use of available resources or move parts to carry out activities that have been prepared. Keywords:Actuating, Al-Quran